The effect of an e-learning-based remedial program on students' learning outcomes: The case of Fraction - Cut, Siti Sabariah; Johar, Rahmah; Mailizar, Mailizar (International Journal of Trends in Mathematics Education Research, 2023)
Students experienced difficulty in studying the topic of fraction during the covid-19 pandemic resulted in incomplete learning so remedial learning was necessary. So far, remedial learning has not been optimally implemented. Therefore, to achieve optimal remedial learning objectives, e-learning based remedial learning is needed. The aims of this study were 1) to find out the effect of e-learning-based remedial learning on the topic of fraction on learning outcomes in junior high schools in Banda Aceh, 2) to examine the improvement in student learning outcomes through e-learning based remedial learning on the topic of fraction on learning outcomes in junior high schools in Banda Aceh. This experimental study used quantitative approach. This study was designed following the pre-experimental design using one-group pretest-posttest. One-group pretest-posttest is a design that includes a pretest followed by treatment and a posttest for one group. The population of this study was all eighth grade students in Banda Aceh. The sample was randomly selected. They were the eighth grade students at four junior high schools whose pretest scores had not yet reached the KKM score of 60. The instruments used were diagnostic test questions and remedial questions on the topic of fraction. Diagnostic and remedial test results data were analyzed with SPSS. The results shows that there is a significant effect of e-learning based remedial learning on the topic of fraction on learning outcomes in junior high schools in Banda Aceh, 2) e-learning based remedial learning on the topic of fraction improves the students’ learning outcomes. The implication of this research is that teachers can implement the remedial learning based on e-learning on other learning topics, so that they has alternative solutions to the problem of implementing remedial learning outside of mathematics learning.